Social support, quality of life, daily living skills and restrictiveness in people with mental disorders in protected homes in Peru - Herrera-López, Vanessa E. (2024)
Objective: To evaluate the quality of life, social support, daily living skills, and level of restrictions, as well as the correlations among these variables in individuals with severe mental disorders residing in protected homes in Peru. Method: A cross-sectional descriptive-correlational study was conducted in 48 protected homes across 21 regions, with a population of 183 residents. A questionnaire was used that included sociodemographic data and four scales: Social support (MOS), Basic everyday living skills (BELS), Mezzich's Quality of Life Index, and the Restrictive Practices Scale. Data were analyzed using Spearman's correlation coefficient and the Mann-Whitney U test. Results: Participants showed significant associations between quality of life, social support (r = 0.29, p < 0.01) and daily living skills, particularly social activities (r = 0.46, p < 0.01) and self-care (r = 0.36, p < 0.01). Restrictiveness was negatively correlated with age (r = -0.202, p < 0.01) and length of residence in the protected home (r = -0.244, p < 0.01): The longer the residents stayed in the home, the lower the restrictiveness and the better their functioning. Significant gender differences were observed in self-care (p = 0.037) and social activities (p = 0.033). Conclusions: The positive associations between quality of life, social support, and daily living skills underscore their importance in protected homes. The reduction in restrictiveness over time suggests possible adaptation and improvement in autonomy.